Pertumbuhan Stek Pucuk Kaliandra (Calliandra calothyrsus Meissn.) Dengan Beberapa Komposisi Media Tanam Dan Konsentrasi Root Up - Permatasari, Putri; Susanto, Dwi; Kusuma, Ratna (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The aims of this research are to know the influence of manure media, ZPT root up and their interaction towards the manure of Kaliandra shoot cuttings. This study used a randomized complete design with two factors i.e. manure media treatment and root up concentration respectively is repeated as many as three times. The data obtained were analyzed using Analysis of Variant (ANOVA) with 95% confidence level and further tested using Duncan test with 95% confidence level. The best results in the treatment of interactions between soil media and manure 200 with a concentration of 200 ppm were able to increase the wet weight of 1.62 gr and dry weight of 0.68 gr. The treatment of soil media and 200 gram manure was able to increase the percentage of live cuttings up to 100%, the height of the plant was 17.45 cm, the leaf size was 7.13 pieces, the wet weight was 1.20 gr and the dry weight was 0.54 gr. Root concentration up to 150 ppm is the best concentration in increasing the number of leaves 7.13 strands, the number of roots is 2.87 strands, the wet weight is 0.54 gr and the dry weight is 0.53 gr